2005
DOI: 10.1159/000089421
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Morules in Colonic Neoplasms: Morules Are Morphologically and Qualitatively Different from Squamous Metaplasia

Abstract: Morules develop in several neoplasms and have been considered as a type of squamous metaplasia despite the absence of keratinization and intercellular bridges. The objective of this study was to clarify the pathological significance of morules and to distinguish morules from squamous metaplasia in colonic neoplasms. Ten cases of morule-associated colonic neoplasms (4 adenocarcinomas, 1 adenoma with carcinoma in situ, and 5 adenomas), and 3 cases of squamous metaplasia in colonic adenocarcinoma were examined mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 54 publications
2
40
1
Order By: Relevance
“…Only occasional strong CD10 positivity has been reported in glands of endometrioid adenocarcinoma (23). However, a previous report failed to show its positivity in endometrial morules (19), and only in one recent article (24) was CD10 positivity shown in morules of colonic neoplasms. We have been able to show identical CD10 strong positivity in morules of well-differentiated fetal adenocarcinoma of the lung.…”
Section: Discussionmentioning
confidence: 94%
“…Only occasional strong CD10 positivity has been reported in glands of endometrioid adenocarcinoma (23). However, a previous report failed to show its positivity in endometrial morules (19), and only in one recent article (24) was CD10 positivity shown in morules of colonic neoplasms. We have been able to show identical CD10 strong positivity in morules of well-differentiated fetal adenocarcinoma of the lung.…”
Section: Discussionmentioning
confidence: 94%
“…They are highly specific in rare neoplasms such as low-grade adenocarcinoma of fetal lung type and the cribriform morular variant of papillary thyroid carcinoma 71. It has been proposed that tumours containing morules reflect a common pathway of carcinogenesis involving molecular alterations of the Wnt-signalling pathway with nuclear β-catenin accumulation 54 71 75 80 81. Also, all morules have in common nuclear expression of CDX258 76 77 and β-oestrogen receptor,75 which appear to be related to their pathogenesis.…”
Section: Epithelial Emcsmentioning
confidence: 99%
“…It has been rarely described with other associated diseases, such as peptic ulcers [4] , tuberculosis [5] , syphilis [6] , corrosive gastritis [7] , extreme cachexia [8] , pernicious anemia [9] and aberrant pancreatic tissue [10] . It may coexist with neoplasms [11,12] . However, there has been no report of squamous metaplasia occurring at an old ulcer scar site in the distal antrum with none of the associated diseases described above.…”
Section: Introductionmentioning
confidence: 99%